Med4way: a Stata command to investigate mediating and interactive mechanisms using the four-way effect decomposition. (16th November 2018) - Discacciati, Andrea; Bellavia, Andrea; Lee, Jane J; Mazumdar, Maitreyi; Valeri, Linda
Abstract: The overall effect of an exposure on an outcome, in the presence of a mediator with which the exposure may interact, can be decomposed into four components that correspond to the portion of the effect that is due: (i) to neither mediation nor interaction; (ii) to just interaction (but not mediation); (iii) to both mediation and interaction; and (iv) to just mediation (but not interaction). This four-way decomposition unifies methods to attribute effects to interactions and methods that assess mediation. We introduce the Stata command med4way to estimate the causal contrasts that arise in this decomposition. Med4way is implemented as a Stata stand-alone command requiring Stata version 10 or higher (StataCorp, College Station, TX, USA), and allows estimating the four-way decomposition using parametric regression models. Med4way can be used when the outcome is continuous, dichotomous, count or survival time, and the mediator is continuous or binary. The command accommodates cohort and case-control designs. We present two examples of application of the command to gain insight on important public health problems. In the first application, we employ med4way to investigate the role of birth outcomes in explaining the effect of maternal exposure to manganese on child neurodevelopment. In the second application, we investigate the role of stage at diagnosis in explaining income disparities in colorectal cancer survival. The command is freely available on GitHub [https://github.com/anddis/med4way ] and has been published under General Public License (GPL) version 3.